Protagonismos femininos na música paraibana: um olhar sobre a trajetória de três mulheres musicistas - Carvalho, Maria Alice Pontes de (2023)
This research brings as central question the trajectories of three women musicians, Nathalia Bellar, Sandra Belê and Glaucia Lima, acting in the city of João Pessoa, from their female protagonism in music from Paraíba, dialoguing with feminist theories, the field of Music and Gender, Ethnomusicology and related areas. In this perspective, this study brings a brief history of women in Brazil, highlighting the paths and struggles of women for the conquest of rights and spaces in society. Subsequently, it makes an overview of the field of Music and Gender, as well as the history of women in music, in order to analyze and discuss the trajectories and protagonism of three women musicians from Paraíba, from the theoretical referential. Furthermore, it brings general data about the quantity of women musicians in João Pessoa, and proposes to discuss measures to confront sexism expanding the debate to think about possibilities of female empowerment in music, aiming for protagonism, as well as to expand the presence of women in the various musical spaces.